2003
DOI: 10.1095/biolreprod.103.020560
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Changes During Onset of Puberty in Male Spring Chinook Salmon, Oncorhynchus tshawytscha1

Abstract: In male salmonids, the age of maturation varies from 1 to 6 years and is influenced by growth during critical periods of the life cycle. The endocrine mechanisms controlling spermatogenesis and how growth affects this process are poorly understood. Recent research has indicated that gonadotropins, 11-ketotestosterone, and insulin-like growth factor I play roles in spermatogenesis in fish. To expand our understanding of the roles of these endocrine factors in onset of puberty, male spring chinook salmon (Oncorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
88
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 49 publications
15
88
0
5
Order By: Relevance
“…To our knowledge, this is the first study localizing specific, androgen-dependent germ cell stages during adult spermatogenesis in teleost fish. This observation correlates well with both the high level of ar mRNA expression in Sertoli cells contacting type A spermatogonia in zebrafish testis (De Waal et al 2008) and the elevation of circulating androgen levels in Chinook salmon at the time when seasonal spermatogonial proliferation starts (Campbell et al 2003).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To our knowledge, this is the first study localizing specific, androgen-dependent germ cell stages during adult spermatogenesis in teleost fish. This observation correlates well with both the high level of ar mRNA expression in Sertoli cells contacting type A spermatogonia in zebrafish testis (De Waal et al 2008) and the elevation of circulating androgen levels in Chinook salmon at the time when seasonal spermatogonial proliferation starts (Campbell et al 2003).…”
Section: Discussionsupporting
confidence: 76%
“…In immature Japanese eel testis containing type A and a few type B spermatogonia only, androgens can induce rapid proliferation of spermatogonia and their terminal differentiation into spermatozoa under tissue culture conditions (Miura et al 1991). Androgen treatment of juvenile male African catfish (Clarias gariepinus) induced precocious testis growth, spermatogonial proliferation and entry into meiosis (Cavaco et al 1998), and the rise of androgen plasma levels in pubertal Chinook salmon (Oncorhynchus tshawytscha) coincided with the start of rapid spermatogonial proliferation (Campbell et al 2003). However, scarce information is available on the role of androgens in adult spermatogenesis in fish.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these roles, Gh has been implicated, directly and indirectly, in the regulation of reproductive processes in several vertebrate taxa. In salmonid fishes, several studies have shown that growth rate at critical periods determines whether animals will undergo gonadal maturation and initiation of spermatogenesis or secondary ovarian follicle growth, an effect that may be mediated through plasma levels of Igf (Campbell et al 2003(Campbell et al , 2006. Gh and Igf1 have also been shown to act on the gonad to stimulate steroid production (Lubzens et al 2010, Schulz et al 2010 and Igf1 is involved in the regulation of final oocyte maturation (Lubzens et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They estimated growth history from annuli of scales in hatchery-arrived chum salmon, and showed that the recent growth rate is the most important factor for oceanic fish to determine whether mature or not mature in the subsequent spawning period. Since the plasma levels of IGF-I correlated well with the growth rates and body sizes in immature and early maturing salmonids (Beckman et al, 1998;Shimizu et al, 2000;Campbell et al, 2003;Campbell et al, 2006), the plasma IGF-I levels may be an important somatotropic signal that interrelated with the onset of spawning migration.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies in salmonid reproduction established that the plasma levels of insulin-like growth factor I (IGF-I), a liver polypeptide that acts as a mediator of growth-promoting action of growth hormone (GH) in teleost fishes (Duan and Hirano, 1992), are increased with body growth during winter and spring, and the seasonal increase in circulating IGF-I was linked to initiation of gametogenesis in male chinook salmon (Campbell et al, 2003) and female coho salmon (Campbell et al, 2006). We thus hypothesized that IGF-I might be involved in reproductive maturation of oceanic chum salmon.…”
Section: Introductionmentioning
confidence: 99%